STIMULATION OF THE EARLY CHILDHOOD LANGUAGE DEVELOPMENT: OPTIMALIZATION OF A MOTHER’S ROLE IN FAMILY EDUCATION - Suardi Suardi; Sulaiman Samad (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study was conducted to examine daily practices of stimulation carried out by mothers at home as an initial support for their children’s language development. This study employed a descriptive design and involved 75 mothers as respondents who wereselected using the non-probability sampling method. The research data were collected using a self-developed questionnaire containing four indicators of early support for children’s language development. The data were analyzed using Microsoft Excel application version 16.10-assisted descriptive statistics. The results of the study showed that daily practices of stimulation carried out by the participants as an initial support for their children’s language development in their first five years of life were included in the ‘very likely’ category. Even so, some practices of stimulation were not properly optimized. This finding promotes the need to increase the ability of mothers to carry out stimulation practices at home so that their involvement in providing initial support for the development of children’s language is more optimal, which in turn can improve the quality of family education at home.